Theatre a very short introduction - Carlson, Marvin A. 1935- (Very short introductions, 2014)
Theatre is one of the longest-standing art forms of modern civilization. Taking a global look at how various forms of theatre - including puppetry, dance, and mime - have been interpreted and enjoyed, this book explores all aspects of the theatre, including its relationship with religion, literature, and its value worldwide